The Hubungan Konsumsi Buah dan Sayur, Aktivitas Fisik, Obesitas Serta Riwayat Keluarga Terhadap Kejadian Hipertensi di Kabupaten Kepulauan Seribu Tahun 2019 - Ica Aisaturrido; Alib Birwin; Rony Darmawansyah Alnur (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2020)
Background: According to riskesdas, prevalence of hypertension based on blood pressure measurement in population aged ≥18 years shows an increase from 2013 by 25.8% to 34.1% in 2018. Based on data from the Non-Communicable Disease Section of the DKI Jakarta Provincial Health Office in 2019, Kepulauan Seribu District has the highest Posbindu PTM achievement for hypertension by 50.61%. Objectives: This study aims to correlate fruit and vegetable consumption, physical activity, obesity and family history of the incidence of hypertension in the Thousand Islands District in 2019. Research Metodes: This study uses secondary data from the DKI Jakarta Provincial Health Office in the form of hypertension screening data in the Thousand Islands District in 2019. The study design in this study was quantitative cross-sectional. A total of 943 samples were taken using simple random sampling technique. Data analysis included univariate and bivariate analyzes using the chi-square test (CI = 95%; α = 0.05). Results: The results of this study indicate there is a relationship between age, gender, lack of physical activity, obesity and family history with the incidence of hypertension with p value 0.000 and there is no relationship between less consumption of fruits and vegetables with the incidence of hypertension with p value 0.190. Conclusion: There is a relationship between age, gender, lack of physical activity, obesity, and family history with the incidence of hypertension in Kepulauan Seribu district in 2019 and there is no relationship between the consumption of fruit and vegetables less with the occurrence of hypertension in Kepulauan Seribu district in 2019.